2015
DOI: 10.1016/j.jagp.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations of PER3 and RORA Circadian Gene Polymorphisms and Depressive Symptoms in Older Adults

Abstract: Background Depressive symptoms are common in older adults and associated with poor outcomes. While circadian genes have been implicated in depression, the relationship between circadian genes and depressive symptoms in older adults is unclear. Methods A cross-sectional genetic association study of 529 single nucleotide polymorphisms (SNPs) representing 30 candidate circadian genes was performed in two population-based cohorts: Osteoporotic Fractures in Men Study (MrOS, n=1270, age 76.58±5.61 years) and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 74 publications
0
14
0
1
Order By: Relevance
“…Rs228697 in PER3 has been linked to morningness–eveningness preference and circadian rhythm sleep disorders, although the length polymorphism/VNTR in PER3 has been linked to stress response and bipolar disorder.. 26 , 27 , 28 In addition, rs12137927 (the same SNP implicated in our study) and rs228644 from PER3 and rs11632098 from RORA were reportedly linked to endorsing the presence of both a modest number (>2 to <6) and a high number of depressive symptoms (⩾6) on the Geriatric Depression Scale as compared with endorsing none-few depressive symptoms (0–2). 29 The variant with association signal of P <0.0001 in the NR1D1 interval is variant rs10305315, located downstream of IGFBP4 ( P =5.99 × 10 −5 ). It remains unclear whether rs10305315 affects the function of NR1D1 (no eQTL evidence from GTEx portal based on GTEx Analysis Release V6).…”
Section: Discussionmentioning
confidence: 99%
“…Rs228697 in PER3 has been linked to morningness–eveningness preference and circadian rhythm sleep disorders, although the length polymorphism/VNTR in PER3 has been linked to stress response and bipolar disorder.. 26 , 27 , 28 In addition, rs12137927 (the same SNP implicated in our study) and rs228644 from PER3 and rs11632098 from RORA were reportedly linked to endorsing the presence of both a modest number (>2 to <6) and a high number of depressive symptoms (⩾6) on the Geriatric Depression Scale as compared with endorsing none-few depressive symptoms (0–2). 29 The variant with association signal of P <0.0001 in the NR1D1 interval is variant rs10305315, located downstream of IGFBP4 ( P =5.99 × 10 −5 ). It remains unclear whether rs10305315 affects the function of NR1D1 (no eQTL evidence from GTEx portal based on GTEx Analysis Release V6).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, by inhibiting ROR γ transcriptional activity and thereby reducing Th17 generation and IL-17A/F production, ROR γ inverse agonists may provide a novel strategy in the treatment of various pathologies in which ROR γ is implicated, including inflammatory, metabolic, endocrine, and autoimmune diseases [ 1 , 2 , 13 , 25 , 257 , 258 ]. Similarly, ROR α antagonists might affect pathologies by inhibiting the generation of ILC2 cells and other physiological functions and be useful in the management of inflammatory, metabolic, and neuropsychiatric disorders [ 1 , 2 , 13 , 25 , 108 , 113 117 , 174 ]. This concept is supported by reports showing that by inhibiting Th17 differentiation and IL-17 production, ROR γ inverse agonists suppress Th17 responses in mice and ameliorate the development of experimental autoimmune encephalomyelitis and imiquimod-induced cutaneous inflammation [ 43 , 244 , 246 , 259 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have indicated an important association between abnormalities in circadian rhythms and patients with mood and neuropsychiatric disorders. Alterations in circadian behavior observed in mice deficient in either ROR α or ROR β receptor [ 122 , 124 , 216 ] and associations between SNPs in RORA and RORB with an increased risk for several neuropsychiatric disorders, including autism spectrum (ASD) and bipolar disorder, schizophrenia, depression, and posttraumatic stress syndrome [ 106 117 , 129 , 130 ], would be consistent with a link between disturbance in the circadian rhythm and these pathologies.…”
Section: Rors and Circadian Rhythmmentioning
confidence: 95%
See 1 more Smart Citation
“…Compete with RORA for binding to the BMAL-1 promoter and repress the BMAL-1 MDD (Soria et al, 2010;Byrne et al, 2014) BD (Kishi et al, 2008;Kripke et al, 2009;Severino et al, 2009) Rora Retinoid-related orphan receptor a (RORA) Works as nuclear hormone receptors. Compete with NR1D1 for binding to the BMAL-1 promoter and activate the BMAL-1 MDD Utge et al, 2010;Maglione et al, 2015) BD Lai et al, 2015;Geoffroy et al, 2016 (Kupfer and Foster, 1972;Kupfer, 1976;Rush et al, 1986;Giles et al, 1987;Pillai, Kalmbach and Ciesla, 2011) BD Euthymia; Increased REM density and proportion of REM sleep, longer sleep onset latency and sleep duration, lower sleep efficiency (Sitaram et al, 1982;Millar, Espie and Scott, 2004;Rocha, Neves and Corrêa, 2013;Geoffroy et al, 2015) Mania; Shortened REM sleep latency, increased REM activity and REM density, reduced total sleep time (Hudson et al, 1988(Hudson et al, , 1992Linkowski and Mendlewicz, 1993) Depression; More fragmented REM sleep periods, shortened REM sleep latency (Gillin et al, 1979;Lauer, Wiegand and Krieg, 1992) longer sleep onset latency, increased proportion of REM sleep, trend toward higher percentage of awakenings in bipolar depression than in unipolar depression (Giles, Rush and Roffwarg, 1986;Jernajczyk, 1986;Fossion et al, 1998)…”
Section: Disclosure Statement and Author Contributionsmentioning
confidence: 99%